Analisis Kepemimpinan Kepala Sekolah dalam Pelaksanaan Program Full Day School pada Sekolah Menengah Pertama di Kabupaten Ponorogo - Fatia Ainur Rosyida; Aris Nurbawani (Edumanagerial, 2023)
Education has an impact on human development, both in terms of academics and character. However, this is not accompanied by the adequate quality of educational institutions. According to the results of a survey on the world's secondary education system in 2019 issued by PISA (Program for International Student Assessment), Indonesia ranked 74th out of 79 countries. To overcome this, it is necessary to improve the quality of education, one of which is to improve the leadership aspects of school principals. This study aims to describe and analyze the role, style, supporting factors and inhibiting factors of the principal's leadership in implementing the full day school program at SMP Negeri 2 Jetis Ponorogo. Data collection techniques are interviews, observation, documentation. The results of this study indicate that: (1) The leadership role of the Principal in implementing the full day school program at SMP Negeri 2 Jetis Ponorogo is educator, manager, administrator, supervisor, leader, innovator, motivator. (2) The principal's leadership style in implementing the full day school program at SMP Negeri 2 Jetis Ponorogo is democratic. (3) The supporting factors for the principal's leadership in implementing the full day school program at SMP Negeri 2 Jetis Ponorogo are the principal has good communication skills, has responsibility for every activity, has good cooperation with the committee, and has good communication skills.